Bringing the other back home: the translation of (un)familiar hybridity - Martín Ruano, M. Rosario (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Increasing migration and growing hybridation have fostered the emergence of new cross-cultural expressive forms that can hardly be considered in ‘national’ terms. The works written (mostly) in English by authors of Hispanic origin seem instead to inhabit the intercultural space of transla¬tion. The question is whether the translations (as usually conceived) of these works remain in an intercultural space. This article will examine the ver¬sions into Spanish of some of these hybrid works in order to determine how this (un)familiar Other is brought home: whether Otherness, difference and hybridity are maintained or neutralized. At least two models can be hinted at: one in which translation seems to return at the service of a ‘national’ literature; one which explores the possibilities of translation as an openly multicultural and multilingual space.